Introduction to Law - Hage, Jaap; Waltermann, Antonia; Akkermans, Bram (Springer, 2017)
The Introduction to Law that you are now holding in your hands is special in the sense that it introduces students to law in general and not to the law of one specific jurisdiction. It has been written with two goals in mind. First, this book is meant to be used in the course Introduction to Law of the Maastricht European Law School. This course aims to provide law students with the global knowledge of the basic legal concepts, elementary philosophy of law, and main fields of law. Since the European Law School does not exclusively focus on the law of one particular European jurisdiction, there is a need for an introductory course that also abstracts from the law of specific jurisdictions. Second, and perhaps more importantly, this book reflects a special way of looking at legal education. We believe that it is of crucial importance for lawyers to be aware of the different ways in which societal problems can be solved and to be able to argue about the advantages and disadvantages of different legal solutions. Being a lawyer involves, on this view, being able to reason like a lawyer, even more than having detailed knowledge of particular sets of rules. The present Introduction to Law reflects this view by paying explicit attention to the functions of rules and to ways of reasoning about the qualities of different legal solutions. Where «positive» law is discussed, the emphasis is on the legal questions that must be addressed by a field of law and on the different kinds of solutions that have been adopted by—for instance—the common law and the civil law tradition. The law of specific jurisdictions is mainly discussed by way of illustration of a possible answer to, for instance, the question when the existence of a valid contract is assumed. This is the second edition of the book. The list of persons who deserve gratitude for their contributions to the present and earlier editions has become too long to mention in full. Therefore we will confine ourselves to those whose role has been particularly important for this second edition. The chapter on tort law is based on an original text written by Gerrit van Maanen, and its present version has benefited from extensive comments by Cees van Dam. Sjoerd Claessens improved the chapter on the law of Europe. Daniel Hannappel has taken care of the format of the text, and Rebecca Kumi has improved the quality of the English. Last but not least, thanks go to all the students and tutors who used this book in our Maastricht Introduction to Law course and reported on their findings.